Fluidic circuit board with modular sensor and valves enables stand-alone, tubeless microfluidic flow control in organs-on-chips. Issue 6 (18th February 2022) - Vivas, Aisen; van den Berg, Albert; Passier, Robert; Odijk, Mathieu; van der Meer, Andries D.
Abstract : Translational Organ-on-Chip Platform (TOP) is a multi-institutional effort to develop an open platform for automated organ-on-chip culture that actively facilitates the integration of components from various developers. Abstract : Organs-on-chips are a unique class of microfluidic in vitro cell culture models, in which the in vivo tissue microenvironment is mimicked. Unfortunately, their widespread use is hampered by their operation complexity and incompatibility with end-user research settings. To address these issues, many commercial and non-commercial platforms have been developed for semi-automated culture of organs-on-chips. However, these organ-on-chip culture platforms each represent a closed ecosystem, with very little opportunity to interchange and integrate components from different platforms or to develop new ones. The translational organ-on-chip platform (TOP) is a multi-institutional effort to develop an open platform for automated organ-on-chip culture and integration of components from various developers. Central to TOP is the fluidic circuit board (FCB), a microfluidic plate with the form factor of a typical well plate. The FCB enables microfluidic control of multiple components like sensors or organ-on-chip devices through an interface based on openly available standards. Here, we report an FCB to integrate commercial and in-house developed components forming a stand-alone flow control system for organs-on-chips. The control system is able to achieve constant and pulsatile flow recirculation through a connected organ-on-chip device. We demonstrate that this system is able to automatically perfuse a heart-on-chip device containing co-cultures of cardiac tissues derived from human pluripotent stem cell-derived cardiomyocytes and monolayers of endothelial cells for five days. Altogether, we conclude that open technology platforms allow the integration of components from different sources to form functional and fit-for-purpose organ-on-chip systems. We anticipate that open platforms will play a central role in catalyzing and maturing further technological development of organ-on-chip culture systems.